2021
DOI: 10.1021/acs.nanolett.1c00396
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Dielectric Screening for Auger Suppression in CdSe/CdS Quantum Dots by Epitaxial Growth of ZnS Shell

Abstract: Auger recombination is the main nonradiative process in multicarrier states of high-quality quantum dots (QDs). For the most-studied CdSe/CdS core/shell QDs, we effectively reduce the biexciton Auger rate by enhancing dielectric screening of band-edge carriers via epitaxial growth of additional ZnS shells. Super volume scaling of negative-trion Auger lifetime for CdSe/CdS core/shell QDs is achieved with the outermost ZnS shells. The volume of CdSe/CdS/ZnS QDs can be less than half that of CdSe/CdS QDs with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…As these ratios are close to the factor of 2 expected for the negatively charged exciton [61][62][63], we tentatively assign τ 2 to the emission of X 1− , with a QY comparable to that of X 0 for both QD species, compatible with the measured emission quantum yields (QY) of 70 % (OA) and 50 % (halide). Large NCs have in fact been shown to have preferred emission through the X 1− channel [55][56][57], consistent with the dominant contribution (60 % of detected photons) of this component in our measured decay curves. The linear power-dependence with saturation of the number of detected photons attributable to τ 2 , Fig.…”
Section: Tablesupporting
confidence: 87%
See 2 more Smart Citations
“…As these ratios are close to the factor of 2 expected for the negatively charged exciton [61][62][63], we tentatively assign τ 2 to the emission of X 1− , with a QY comparable to that of X 0 for both QD species, compatible with the measured emission quantum yields (QY) of 70 % (OA) and 50 % (halide). Large NCs have in fact been shown to have preferred emission through the X 1− channel [55][56][57], consistent with the dominant contribution (60 % of detected photons) of this component in our measured decay curves. The linear power-dependence with saturation of the number of detected photons attributable to τ 2 , Fig.…”
Section: Tablesupporting
confidence: 87%
“…4 c and g, again suggesting single-exciton emission. As it has been surmised previously that the emission lifetime of the positively charged exciton X 1+ is shorter than that of X 1− (our τ 2 candidate) in CdSe/CdS [62], CdSeS/ZnS NCs [40] and CdSe/CdS/ZnS [57], we assign τ 3 to the emission of X 1+ . Finally, the number of photons detected from the fastest component (τ 4 < 0.5 ns) are the only ones whose power dependence is a convex function, see Fig.…”
Section: Tablementioning
confidence: 84%
See 1 more Smart Citation
“…In previous studies, tuning the rates of Auger recombination could be mostly achieved by changing the size of the core and shell, but the huge volumes and reduced spectral tunability would limit applications in some aspects. Peng et al [ 47 ] reported an additional layer of ZnS shell with a large bandgap upon CdSe/Cds core/shell NC, the outermost shell can simultaneously restrict both conduction band minimum and valance band maximum wave functions away from the interface and enhance dielectric screening for Auger suppression without altering delocalization of the wave functions by changing the size of NCs (the band alignment is shown in Figure a). They synthesized CdSe/4CdS/2ZnS core/shell/shell QDs, which exhibited sharp absorption peak features and narrow emission peak, and also possessed near unity PL QY (92%) and monoexponential PL decay dynamics at a single‐exciton regime.…”
Section: Strategies For Band Alignment Engineeringmentioning
confidence: 99%
“…Reproduced with permission. [ 47 ] Copyright 2021, American Chemical Society. d) Schematic illustration of the band alignment of CdS/ZnSe/ZnS heterostructures.…”
Section: Strategies For Band Alignment Engineeringmentioning
confidence: 99%